Re-evaluating the Contribution and Legacy of Hedley Bull - Emerson Maione Souza (Brazilian Political Science Review, 2008)
The article aims, in the first instance, to make a detailed analysis of the work of Hedley Bull, approaching the main themes and concepts developed by him. Secondly, it aims to re-evaluate the potential of the author’s contribution, given the new conditions of the post-Cold War period. With this in mind, the article critically analyses the most recent interpretations of this work, which seek to highlight its critical and normative potential, as well as to dissociate it from the realist tradition in international relations. These two facts differentiate the new commentators from older ones and reaffirm the continuing relevance of Hedley Bull’s work, the latter being the article’s chief conclusion.